Evaluation of an automated, computerized system (automicrobic system) for Enterobacteriaceae identification. - Burdash, N M (1981)
The automated and computerized AutoMicrobic system (AMS; Vitek Systems, Inc., subsidiary of McDonnell Douglas, Hazelwood, Mo.) was evaluated as a means of identifying the Enterobacteriaceae. The Micro-ID system (General Diagnostics, Morris Plains, N.J.) and, when necessary, conventional tubed media were used for comparison. Identification by AMS and Micro-ID differed in only 12 of 1,528 isolates (0.8%). Disagreements occurred primarily with Enterobacter spp. Precision testing of the AMS showed only 1 of 72 tests (1.4%) deviating from the expected. The AMS was found to be an accurate and precise method for the identification of Enterobacteriaceae.